Human Resource Development In An Effort To Improve Service Towards Customer Satisfaction At PT. Pegadaian (Persero) Ciparay Branch - Fihlal Abdul Azis; Adji, Widwi Handari (Pascasarjana STIE Miftahul Huda, 2025)
This study aims to analyze the extent to which Human Resource Development (X1) affects two important variables, namely Service Quality (Y1) and Customer Satisfaction (Y2). In the process, a quantitative approach is used as the main method, as well as applying the Descriptive Verification approach, in the sampling technique using Random Sampling because the Service is dynamic and the number of customers changes. The results of this study show a simultaneous influence on Variable Y1 and Variable Y2 on Variable (X1), with the results of SPSS 30 data processing of 76.2% and the remaining 23.8% coming from other variables that are outside the scope of this study and are not analyzed further. This indicates that although Human Resource Development has a significant role in improving service quality and customer satisfaction, there are also other external factors that need to be considered in further research to obtain a more comprehensive picture of the determinants of service quality and customer satisfaction as a whole.